Microdeletions and Microduplications in Patients with Congenital Heart Disease and Multiple Congenital Anomalies - Goldmuntz, Elizabeth (Congenit Heart Dis, 2011)
OBJECTIVE: Multiple genetic syndromes are caused by recurrent chromosomal microdeletions or microduplications. The increasing use of high-resolution microarrays in clinical analysis has allowed the identification of previously undetectable submicroscopic copy number variants (CNVs) associated with genetic disorders. We hypothesized that patients with congenital heart disease and additional dysmorphic features or other anomalies would be likely to harbor previously undetected CNVs, which might identify new disease loci or disease-related genes for various cardiac defects. DESIGN: Copy number analysis with single nucleotide polymorphism-based, oligonucleotide microarrays was performed on 58 patients with congenital heart disease and other dysmorphic features and/or other anomalies. The observed CNVs were validated using independent techniques and validated CNVs were further analyzed using computational algorithms and comparison with available control CNV datasets in order to assess their pathogenic potential. RESULTS: Potentially pathogenic CNVs were detected in twelve of 58 patients (20.7%), ranging in size from 240 Kb to 9.6 Mb. These CNVs contained between 1 and 55 genes, including NRP1, NTRK3, MESP1, ADAM19, and HAND1, all of which are known to participate in cardiac development. CONCLUSIONS: Genome-wide analysis in patients with congenital heart disease and additional phenotypes has identified potentially pathogenic CNVs affecting genes involved in cardiac development. The identified variant loci and the genes within them warrant further evaluation in similarly syndromic and nonsyndromic cardiac cohorts.